Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Appendix A - Review - A.1 Algebra Essentials - A.1 Assess Your Understanding - Page A12: 117



Work Step by Step

Let $x=2$. Then by substitution, we have $$ 2x^3-3x^2+5x-4=2(2)^3-3(2)^2+5(2)-4\\=16-12+10-4=10 .$$ When $x=1$, we have $$ 2x^3-3x^2+5x-4=2(1)^3-3(1)^2+5(1)-4\\=2-3+5-4=0 .$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.